2019
DOI: 10.1136/leader-2019-000135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of a national clinical leadership fellow scheme

Abstract: BackgroundThe drive towards engaging UK doctors in clinical leadership and management has involved a number of initiatives at various levels, including specific fellowships for doctors in training which enable them to take a year out of programme to work with senior leaders on service improvement or policy development projects.ObjectivesThis paper reports on the findings of an impact evaluation of a national Fellowship Scheme for doctors in training. The evaluation aimed to determine: What were the key success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Behavioural changes were objectively demonstrated in higher reliability studies through observed changes in behaviour,26 27 39–43 promotions,44 45 increased responsibilities or titles28 46–49 and project completion 50–52. Subjective changes in behaviour included improved communication,39 influence,50 delegation,27 collaboration,53 involvement in service improvement47 and application of skills learnt or improved leadership in general 39 40 54–57. These changes were indicated through interviews, free text questionnaire responses and behavioural self-assessments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural changes were objectively demonstrated in higher reliability studies through observed changes in behaviour,26 27 39–43 promotions,44 45 increased responsibilities or titles28 46–49 and project completion 50–52. Subjective changes in behaviour included improved communication,39 influence,50 delegation,27 collaboration,53 involvement in service improvement47 and application of skills learnt or improved leadership in general 39 40 54–57. These changes were indicated through interviews, free text questionnaire responses and behavioural self-assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Organisational outcomes in higher reliability studies (Kirkpatrick level 4) were defined prospectively and in most cases were objectively demonstrated through leadership project impact evaluations. Projects achieved a range of outcomes, including reduced waiting times,50 improved patient care46 50 and cost savings 27 46 47 50. By assessing the financial impact of projects completed during the intervention and relating this to programme costs, one higher reliability study reported a 364% financial return-on-investment (ROI) 27.…”
Section: Resultsmentioning
confidence: 99%
“…Fellowships exist at national, regional and local levels across the four UK nations, are highly competitive and while still relatively novel, emerging evaluations highlight their impact on individuals, organizations and the wider health service. [46][47][48][49][50][51] Most fellowships include a funded formal "taught" component (some of which are award bearing programs such as a postgraduate certificate), an internship with one or more senior healthcare leaders, and a range of experiential learning including visits to other organizations, networking events and conference attendance. 52 Fellowships often require taking one or more years out of program however, and can negatively impact on the Fellows' return to training, with a significant mind-set adjustment required after working out of program with senior leaders in non-clinical environments, and then going back to being simply "one of many" trainees.…”
Section: Academic Careers In Leadership and Managementmentioning
confidence: 99%
“…Despite the evidence that medical leadership and engagement improves outcomes and performance, 53 Fellows have reported that often clinicians do not understand what they have been doing on their fellowship and how they could subsequently use their new skills to engage in service and quality improvements', with some reporting indifference, even hostility towards them. 46 Equity of access to leadership development is also highly variable, and while various funded opportunities are available, they often come at a direct and not insignificant personal and financial cost to trainees with much more needed to be done to ensure an inclusive approach.…”
Section: Academic Careers In Leadership and Managementmentioning
confidence: 99%
“…11 Conversely, having a year out of programme can provide the valuable opportunity to test out leadership skills in a new environment, forge new connections with employees working across the public sector -and, in some cases, can open the door to a different career path in policy or the civil service. 12 If you are currently on a training scheme, remember to apply for prospective approval to go out of programme. Discuss this with your educational supervisor and training programme director well in advance, and ensure you complete the necessary forms for Annual Review of Competency Progression purposes.…”
Section: Applying For Fellowshipsmentioning
confidence: 99%